Effect of bacterial products on human ciliary function in vitro. Issue 2 (February 1985) - Wilson, R; Roberts, D; Cole, P
Abstract : Ciliary activity protects the respiratory tract against inhaled particles, including bacteria, by transporting them trapped in mucus towards the pharynx. We have studied the effect of bacteria (Haemophilus influenzae, Staphylococcus aureus, and Pseudomonas aeruginosa) on human nasal cilia, measuring their in vitro ciliary beat frequency by a photometric technique. Supernatant fluids were obtained from 18 hour broth cultures by centrifugation alone, by filtration, and by lysis. Supernatants obtained from Ps aeruginosa and H influenzae caused a significantly lower ciliary beat frequency than controls (broth alone). Slowed cilia were dyskinetic and at times of maximal slowing ciliostasis occurred in some areas of the epithelium. A dose related effect was demonstrated. Abrogation of cilioinhibitory properties was achieved by heating the lysate to 56 degrees C for 30 minutes and by allowing the filtrate to stand at 37 degrees C for 120 minutes. Staphylococcal products were not cilioinhibitory. It is concluded that Ps aeruginosa and H influenzae release a factor (or factors) which causes slowing of human nasal cilia in vitro. The role of this factor in the pathogenesis of infection is discussed.